STUDI KOMPERASI MODEL PEMBELAJARAN TALKING STICK DAN SNOWBALL THROWING TERHADAP HASIL BELAJAR BERDASARKAN TAKSONOMI BLOOM - Nabilah, Ummi; Saragih, Marlindoaman; Komarul Huda, Muhammad (Program Studi Pendidikan Biologi, Fakultas Keguruan Dan Ilmu Pendidikan Universitas Simalungun, 2022)
This study aims to determine the differences in student learning outcomes and the magnitude of the differences in student learning outcomes using the Talking Stick and Snowball Throwing learning models on the excretory system in class VIII of Bina Guna Tanah Jawa Private Junior High School in the 2021/2022 academic year. This study is a quasi-experimental study with different treatments given to each class. The research sample was taken using a saturated sampling technique (census) consisting of two classes: class VIII-1 was designated as experimental class 1 using the Talking Stick learning model, with 32 students, while class VIII-2 was designated as experimental class 2 using the Snowball Throwing learning model, with 32 students, resulting in a total sample of 64 students. Data analysis was carried out by finding the mean (X̅ ), standard deviation (S), and hypothesis testing (t-test) at a significance level of α = 0.05. The research results obtained an average post-test score of 86.56 for experimental class 1 and 85.93 for experimental class 2, with a difference in learning outcomes of 0.63. The results of the hypothesis testing (t-test) obtained thitung (1.708) > ttabel (1.669) at a significance level of α = 0.05 and degrees of freedom (dk) = 32. Therefore, Ho is rejected and Ha is accepted, meaning there is a difference in student learning outcomes using the Talking Stick and Snowball Throwing learning models on the excretory system topic for class VIII at Bina Guna Tanah Jawa Private Junior High School in the 2021/2022 Academic Year. It was concluded that there is a difference in student learning outcomes using the Talking Stick and Snowball Throwing learning models on the excretory system topic in class VIII at Bina Guna Tanah Jawa Private Junior High School in the 2021/2022 Academic Year.